C-peptide and cardiovascular system - Bawaskar, Himmatrao S.; Bawaskar, Parag Himmatrao; Bawaskar, Pramodini Himmatrao (International Journal of Research in Medical Sciences, 2017)
Background: C-peptide and insulin are secreted by pancreatic beta cells in equimolar concentrations. C- Peptide is associated with increased risk of cardiovascular disease. Methods: Routine outpatient department patients were investigated for serum C-peptide, Diabetes, Ischemic heart disease, hypertension and skin lesion acanthosis negrican. Results: Total ninety five patients enrolled in study of these peptide level 2, 2 to5 and >5 found in 22,46,27 patients respectively, with diabetes mellitus in 21 (95%), 39(55%) and 24 (89%), ischemic heart diseases 1(5%), 15(33%), 13(48%) , hypertension 9(41%), 20(44%), 12(45%), acanthosis negrican 9 (41%), 27 (59%), 21 (78%), family history 1 (5%), 18 (39%), 11 (41%) respectively. Conclusion: Significant incidence of hypertension and ischemic heart disease is related to raised level of circulating C-peptide.